2021
DOI: 10.3390/ijms22189818
|View full text |Cite
|
Sign up to set email alerts
|

The miR-133a, TPM4 and TAp63γ Role in Myocyte Differentiation Microfilament Remodelling and Colon Cancer Progression

Abstract: MicroRNAs (miRNAs) play an essential role in the regulation of a number of physiological functions. miR-133a and other muscular miRs (myomiRs) play a key role in muscle cell growth and in some type of cancers. Here, we show that miR133a is upregulated in individuals that undertake physical exercise. We used a skeletal muscle differentiation model to dissect miR-133a’s role and to identify new targets, identifying Tropomyosin-4 (TPM4). This protein is expressed during muscle differentiation, but importantly it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 76 publications
1
5
0
Order By: Relevance
“…31 The results obtained from the current study showed that miR-133a is downregulated in CRC and that it has perfect significance when related to tumor staging, grading and lymph node metastasis with sensitivity 98.6% and specificity 88% suggesting its role as important biomarker for diagnosis and prognosis of CRC consistent with Wan et al, 2014 and Caporali et al, 2021. 32,33 In the current study, miR-133a expression was considerably decreased in the serum of CRC patients with late stage and low grade, consistent with earlier reports by Luo et al, 2013, 34 which also contradicts many studies, indicating that miR-133a is not simply an oncogene as many papers reported. 31 MiR-574-3p has been verified as a tumor suppressor in several cancers such as prostate cancer, bladder cancer, gastric cancer, ovarian cancer and chronic myeloid leukemia.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…31 The results obtained from the current study showed that miR-133a is downregulated in CRC and that it has perfect significance when related to tumor staging, grading and lymph node metastasis with sensitivity 98.6% and specificity 88% suggesting its role as important biomarker for diagnosis and prognosis of CRC consistent with Wan et al, 2014 and Caporali et al, 2021. 32,33 In the current study, miR-133a expression was considerably decreased in the serum of CRC patients with late stage and low grade, consistent with earlier reports by Luo et al, 2013, 34 which also contradicts many studies, indicating that miR-133a is not simply an oncogene as many papers reported. 31 MiR-574-3p has been verified as a tumor suppressor in several cancers such as prostate cancer, bladder cancer, gastric cancer, ovarian cancer and chronic myeloid leukemia.…”
Section: Discussionsupporting
confidence: 86%
“… 31 The results obtained from the current study showed that miR-133a is downregulated in CRC and that it has perfect significance when related to tumor staging, grading and lymph node metastasis with sensitivity 98.6% and specificity 88% suggesting its role as important biomarker for diagnosis and prognosis of CRC consistent with Wan et al, 2014 and Caporali et al, 2021. 32 , 33 …”
Section: Discussionmentioning
confidence: 99%
“…Abnormal activation of the Hedgehog signaling pathway can lead to the occurrence and progression of colorectal cancer (Guo et al, 2022). The enhancement of mitotic spindle and myogenesis pathways indicated that cell division, microfilament cytoskeleton, and stress fibers formation process were active (Caporali et al, 2021). The downregulation of pancreas beta cells, oxidative phosphorylation, peroxisome, and mTORC1 signaling showed the disturbance of nutrient metabolism of samples in the high-risk subgroup.…”
Section: Discussionmentioning
confidence: 99%
“…The genes that produce miR-133a and miR-1 are clustered together, with the two miRNAs transcribed as a single primary transcript (44). In skeletal muscle, miR-133a stimulates muscle growth by reducing myoblast differentiation, possibly through downregulation of tropomyosin-4, an actin binding component of the cytoskeleton (45). In cardiac tissue, miR-133a is linked to hypertrophy, although so far only as a marker of disease (e.g.…”
Section: Muscle-enriched Circulating Mirnas Levels Are Altered With A...mentioning
confidence: 99%